NILAI NILAI PENDIDIKAN ISLAM DALAM TRADISI MAUDU’ LOMPOA DI CIKOANG KABUPATEN TAKALAR - Hattajur; Muhammad Amri; Muhammad Yahdi (Istiqra: jurnal hasil penelitian, 2025)
The Maudu’ Lompoa tradition is a Maulid Nabi Muhammad SAW celebration that has been practiced for generations by the community of Cikoang Village, Takalar Regency, South Sulawesi. This tradition represents an integration of Islamic teachings and local wisdom. Although Maudu’ Lompoa has been debated among some Islamic scholars and is sometimes perceived as a form of bid‘ah, substantively it contains Islamic educational values that remain relevant to the socio-religious life of the community. This study aims to examine the implementation of the Maudu’ Lompoa tradition and to identify the Islamic educational values embedded within it. The research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the Maudu’ Lompoa procession consists of several ritual stages, including purification rites, food preparation, communal prayers, and the distribution of alms. A distinctive feature of this tradition is the preparation of Julung-Julung, decorated wooden boats filled with agricultural products and daily necessities that are shared with the community as a form of charity. The Islamic educational values reflected in the Maudu’ Lompoa tradition include ilahiyah values manifested in the strengthening of faith and love for the Prophet Muhammad SAW, ubudiyah values expressed through purification and almsgiving, muamalah values embodied in mutual cooperation and social solidarity, and aesthetic values reflected in cultural creativity and artistic expression. This study contributes to Islamic education scholarship by demonstrating how local cultural traditions function as effective media for internalizing Islamic values within community life.